1942
DOI: 10.1111/j.1939-0025.1942.tb05899.x
|View full text |Cite
|
Sign up to set email alerts
|

Relation of infants' weight and body build to locomotor development.

Abstract: 1 Since the preparation of this article, Dr. Wayne Dennis has kindly lent the authors a copy of his paper on walking, which he presented at the Eighth American Scientific Congress (xgdo), to be published in the Am. J. Dis. Child ( I ) . He analyzed the onset of walking in 25 puberty praecox cases and found the average and range of their walking ages to be entirely normal. Thus there appears to 234 This document is copyrighted by the American Psychological Association or one of its allied publishers.This articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1943
1943
1947
1947

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Certain evidence presented by Peatman and Higgons (23,24) might seem contrary to this conclusion. These authors studied the motor development of a total of 349 infants who received exceptionally good pediatric care, whose health records were excellent, and whose growth rate was above the standard norms.…”
Section: Ossification and Strengthmentioning
confidence: 86%
“…Certain evidence presented by Peatman and Higgons (23,24) might seem contrary to this conclusion. These authors studied the motor development of a total of 349 infants who received exceptionally good pediatric care, whose health records were excellent, and whose growth rate was above the standard norms.…”
Section: Ossification and Strengthmentioning
confidence: 86%
“…Jokl and Cluver (36) reported a number of athletes who have had serious physical deficiencies but have compensated for them and made outstanding records. Peatman and Higgins (51) found no re lation between body build and age at sitting, standing, and walking alone in a group of 349 healthy infants. Weech and Campbell (62), however, found that when rates of growth are studied, the "infant who is expanding rapidly in physical size develops .…”
Section: Relation Of Motor Abilities To Other Factorsmentioning
confidence: 97%
“…Infancy and early childhood Woodbury (1921); Freeman (1933); Bayley and Davis (1935); Bayley (1936): Bakwin and Bakwin (1936); Gesell and Thompson (1938); Peatman and Higgons (1938); Davenport (1938); Boyd (1941); Robinow (1942).…”
Section: Infancy and Late Childhoodmentioning
confidence: 99%